The barriers and facilitators influencing the effectiveness of high secure forensic care: a critical realist qualitative study - Guite, John P. (2022)
This thesis examines the barriers and facilitators influencing the effectiveness of high secure forensic care. Forensic psychiatric care is concerned with the assessment and treatment of mentally disordered offenders who are detained under various sections of the Mental Health Act. A prime function of forensic psychiatric care is the management of risk, and the protection of the public. In England, high secure forensic care is provided at Rampton, Broadmoor and Ashworth hospitals, and to be admitted to high secure care patients must be considered a grave and immediate danger to the public or themselves. This risk management places restrictions on the lives of patients however, there is a need to balance the management of risk, with promoting recovery and rehabilitation of patients with the need to maintain safety and security.